Histoplasmose do esôfago: Relato de caso - Henry, Maria Aparecida Coelho de Arruda [UNESP]; Mendes, Elson Felix; Saad, Luiz Henrique Cury [UNESP]; Rodrigues, Paulo Antônio [UNESP]; Gonçalves Júnior, Irio [UNESP] (My University, 1996)
The authors report a case of a patient with complaint of progressive disphagia. Stenoses of lower third of esophagus was revealed by radiological and endoscopic examinations. Fungi were showed in biopsy of lesion, with demonstration of Histoplasm capsulate by tissue culture. Endoscopic dilatation was performed because especific medical treatment failed but esophageal rupture was observed. Partial esophagectomy was performed with symptoms remission.
Keywords: Esophageal diseases; Histoplasmosis; Therapy; fluconazole; itraconazole; ketoconazole; adult; case report; dysphagia; endoscopy; esophagus resection; esophagus rupture; esophagus stenosis; histoplasma capsulatum; histoplasmosis; human; male; esophagus disease; microbiology; middle aged; Esophageal Diseases; Esophagectomy; Humans; Male; Middle Aged